Penggunaan Model Pembelajaran Berbasis Collaborative Learning Berpengaruh terhadap Hasil Belajar Akuntansi - Rosmiati Rosmiati (Universitas Batanghari Jambi, 2021)
The cause of the low completeness of learning in accounting subjects is due to the inappropriate learning model used in the classroom and the lack of learning media which results in students being less interested in learning and it has implications for students' lack of understanding of the material and learning outcomes themselves. The purpose of this study was to determine the effect of using a collaborative learning-based learning model on the accounting learning outcomes of students in class XI IPS at SMA Negeri 5 Jambi City. This study used a quasi-experimental approach with a pretest-posttest control group comparision design. The subjects in this study were students of class XI IPS 5 as the experimental class and XI IPS 3 as the control class with the data analysis technique of learning outcomes using the t-test. So it can be concluded that the average accounting learning outcomes of class XI IPS students who are taught using a Collaborative Learning-based learning model is 75.33 higher than the average learning outcomes of class XI IPS students in accounting subjects taught conventionally is 62., 8. The results of the t-test showed that the coefficient tcount> ttable or 5.048> 2.039. Thus it can be interpreted that there is an effect of the use of Collaborative Learning-based learning models on the learning outcomes of accounting students in class XI IPS at SMA Negeri 5 Jambi City.